PENGARUH INSTAGRAM TERHADAP KEPUTUSAN BERKUNJUNG GENERASI Z DI PUNCAK KAI’SANTI TOMOHON - Steven Yones Kawatak; Roosalina Hera Lucia; Johanes Albert Niaboy (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Tourism promotion on Instagram has been increasingly used by tourism destination administrators to promote their attractions and facilities to increase the numbers of visitors. Generation Z dominates the number of Instagram users in Indonesia, which in turn makes them as one of the most potential target markets in tourism promotion. This research aims to ascertain the impact of promotion on Instagram on Generation Z’s decision to visit Puncak Kai’santi located in Tomohon City. As the determining factors of the effectiveness of promotion on Instagram in this research, the researchers choose Context, Communication, Collaboration, and Connection as the independent variables, while the dependent variable is the Generation Z’s decision to visit this destination. To determine the relationships between variables, the researchers utilize the Multiple Linear Regression technique to analyze data collected from 60 respondents. The result shows that simultaneously, all independent variables have a significant effect on Generation Z’s decision to visit. However, when the data is analyzed partially, the result shows that Collaboration is the only variable that affects Generation Z’s decision to visit Puncak Kai’santi.